Application and exploration of Traditional Chinese Medicine nursing for COVID-19 patients in convalescence (中医护理在新型冠状病毒感染恢复期的应用与探索) - ZHOU Jie (周洁); CHEN Hong (陈宏); DENG Jianhua (邓建华); LI Suqian (李苏茜); LI Ye (李野); E Haiyan (鄂海燕); ZHENG Ping (郑萍); TANG Ling (唐玲) (Association of Integrative Nursing, 2023)
The COVID-19 infection belongs to the category of "blight" in Traditional Chinese Medicine. The course of illness is generally about 7 days, and the recovery period is crucial for COVID-19 patients. This paper comprehensively summarized the application of Traditional Chinese Medicine nursing in the recovery period of novel coronavirus infection from the aspects of moxibustion, exercise therapy, Traditional Chinese Medicine emotional therapy, acupoint massage, diet nursing, etc. , so as to provide reference for further research. (新型冠状病毒感染属于中医"疫病"范畴, 病程一般约7 d, 恢复期对于患者来说至关重要。本文从艾灸、运动调护、中医情志疗法、穴位按摩、饮食护理等方面总结了中医护理在新型冠状病毒感染恢复期的应用, 为进一步研究提供参考。)